STUDY OF PEST ATTACK INTENSITY ON COMMERCIAL STRAWBERRIES (Fragaria x ananassa) - Putri Cahya Angraeny; Agus Suprapto; Yunimar Yunimar (Universitas Tidar, 2018)
This study aims to determine the types of pests that attack the various stages of plant development strawberries and measure the extent of damage to strawberry plants caused by pests. These observations were made in Tlekung Experimental Station, Research Institute for Citrus and Subtropical Fruit, Batu municipality, East Java in July until September 2018. The strawberry plants were observed consisting of three varieties, namely Sweet Charlie (SC), Dorit (DR), and Early Bright (EB). Each variety consisted of 20 plants in the vegetative and generative phases with different planting locations were in the screen house and open fields. Observations intensity of pest attacks were divided into three, namely the intensity of leaf-eating pests, pest mites and pests of fruit eaters. The results showed pests that attack strawberry plants consist of the phylum Mollusca and Arthropods. The highest intensity level of pest attacks occur at the location of strawberry cultivation in open fields than the strawberries grown in the screen house that is the pest mites reached 91,25%, which is included in the category very heavy attack on the variety SC. SC varieties were most susceptible varieties against leaf-eating pests and pest mites. Susceptibility to pests highly dependent on the age of the plant, character growth, and morphological characters.